2009
DOI: 10.4310/jdg/1242134371
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic Calabi-Yau manifolds, minimal surfaces and the hyperbolic geometry of the conifold

Abstract: Given an SO(3)-bundle with connection, the associated two-sphere bundle carries a natural closed 2-form. Asking that this be symplectic gives a curvature inequality first considered by Reznikov [34]. We study this inequality in the case when the base has dimension four, with three main aims.Firstly, we use this approach to construct symplectic six-manifolds with c 1 = 0 which are never Kähler; e.g., we produce such manifolds with b 1 = 0 = b 3 and also with c 2 · [ω] < 0, answering questions posed by Smith-Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(99 citation statements)
references
References 41 publications
(77 reference statements)
0
99
0
Order By: Relevance
“…In [18], Reznikov observed that Z also carries a natural closed 2-form ω, whose restriction to each fibre of π is the area form. Asking for ω to be symplectic gives a curvature inequality for g, which was first investigated by Reznikov [18] and later described explicitly in [11]. (In fact, this can be seen as a special case of the 'fat connections' introduced much earlier by Weinstein [19].)…”
Section: Statement Of the Main Resultsmentioning
confidence: 96%
“…In [18], Reznikov observed that Z also carries a natural closed 2-form ω, whose restriction to each fibre of π is the area form. Asking for ω to be symplectic gives a curvature inequality for g, which was first investigated by Reznikov [18] and later described explicitly in [11]. (In fact, this can be seen as a special case of the 'fat connections' introduced much earlier by Weinstein [19].)…”
Section: Statement Of the Main Resultsmentioning
confidence: 96%
“…From this data only we show how to construct very natural structures on twistor space, namely the 1-form τ , some associated connection on O(n) bundle and the triplet (J A , ω A , g A ) of compatible almost complex structure, 2-form and Euclidean metric on twistor space of proposition 1. We also review, from [14], some symplectic structure that is naturally constructed from the connection. Finally we investigate the condition for integrability of the almost complex structure as well as the condition for which the triplet (J A , ω A , g A ) is Kähler.…”
Section: Proposition 2 Pure Connection Non-linear Graviton Theoremmentioning
confidence: 99%
“…This is a well known construction (cf [16]) and we here use the terminology of [14], [15]. We also briefly recall how to write equations for full Einstein gravity in terms of connections from [3], [25].…”
Section: Definite Connections and Gravitymentioning
confidence: 99%
See 2 more Smart Citations